2014
DOI: 10.1210/jc.2013-3593
|View full text |Cite
|
Sign up to set email alerts
|

A HomozygousCaSRMutation Causing a FHH Phenotype Completely Masked by Vitamin D Deficiency Presenting as Rickets

Abstract: CaSR mutations causing mild functional impairment can lead to FHH, even in homozygous patients. The skeletal deformities in the index case were mainly due to severe vitamin D deficiency, and the CaSR mutation did not appear to have played a major independent role in the skeletal phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Inactivating mutations of the CASR lead to a right-shifted dose-response curve for extracellular calcium with a higher 'setpoint' resulting in hypercalcemic diseases (6,7,8). The phenotype depends on the degree of overall functional impairment of extracellular calcium sensing by CASRdependent mechanisms.…”
Section: Mutations Causing Loss Of Casr Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inactivating mutations of the CASR lead to a right-shifted dose-response curve for extracellular calcium with a higher 'setpoint' resulting in hypercalcemic diseases (6,7,8). The phenotype depends on the degree of overall functional impairment of extracellular calcium sensing by CASRdependent mechanisms.…”
Section: Mutations Causing Loss Of Casr Functionmentioning
confidence: 99%
“…There are, however, exceptions from this rule. Homozygous CASR mutations leading to only a mild overall impairment of extracellular calcium sensing may cause a FHH-like phenotype (8,12,13,14), whereas heterozygous CASR mutations causing more pronounced functional impairment can lead to neonatal hyperparathyroidism (NHPT) (15,16,17). Recently it has been found that inactivating mutations in the CASR associated G protein alpha 11 (GNA11) and in the adaptor-related protein complex 2 sigma 1 subunit (AP2S1) can also cause familial hypocalciuric hypercalcemia (FHH types 2 and 3) (18,19,20).…”
Section: Mutations Causing Loss Of Casr Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…FHH is characterized biochemically by lifelong modest elevation of the serum calcium concentration with a relatively mismatched hypocalciuria and normal or mildly elevated circulating parathyroid hormone (PTH) level that is not suppressed by the hypercalcemia. 1,2 Individuals with FHH are usually asymptomatic, and the disorder is considered benign. FHH is associated with heterogeneous inactivating mutations in the calcium-sensing receptor ( CaSR ) gene.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report described a patient who developed severe adolescent rickets due to vitamin D deficiency. 2 Another report considered that vitamin D deficiency modulates the severity of FHH. 3 …”
Section: Introductionmentioning
confidence: 99%